Pavement defect detection with deep convolutional neural network - Chan, Zhen Yi (Nanyang Technological University, 2023)
Automatic inspection and defect detection using visual data such as images and videos is currently an active research topic in machine vision. The technique is widely adopted in industries, for example, for surface defect detection. The basic idea is to examine visual patterns from images of the manufactured surfaces to detect flaws. This has the advantages of overcoming the limitations of the traditional inspection approaches that depend heavily on humans and improving the efficiency and performance of the inspection.